PREVALENSI KONSUMSI ROKOK PRIA USIA 18 - 64 TAHUN DENGAN HIPERTENSI DI DESA SUSUT, KABUPATEN BANGLI BALI TAHUN 2014 - Bianca Jeanne (Intisari Sains Medis, 2016)
Hypertension is a classic problem that contributes to increased morbidity and mortality due to its complications. A good management of hypertension can reduce the risk of stroke, coronary heart disease, congestive heart failure, and death significantly. Factors that influence the occurrence of hypertension were divided into two major group; unmodifying factors such as sex, age, and genetic factors, and modifying factors such as diet, exercise habits and others. Hypertension happened due to the combination of these risk factors together, in other words, one risk factor alone is not sufficient to cause hypertension. Smoking has long been associated with high numbers of morbidity and mortality in cardiovascular disease. It works together with hypertension and dyslipidemia to increase the incidence of myocardial infarct. A descriptive cross-sectional study conducted on 89 people in the Susut village of Bangli, which is selected with non-probability sampling methods (convenience sampling). Each sample was measured to obtain the data of blood pressure. Interviews were conducted to obtain data about the characteristics of respondents and pattern of cigarette consumption in men with hypertension in Susut village, Bangli Regency. Data were analyzed descriptively. Results of the data analysis shows that the overall sample have hypertension that is a number of 33 people (37%) and the remaining 56 people (63%) did not have hypertension.And for the pattern of cigarrete consumption in hypertensive men aged 18-24 years in Susut village, Bangli obtained tend to be current smokers (48.4%). The severity of cigarrete consumption tend to be light smokers (88.8%). All types of cigarettes consumed is filter type (100%) and for years of cessation in ex-smokers tend to be less than 10 years (80%).Â